PENGARUH SOLAR PROTON EVENT JANUARI 2005 TERHADAP PENIPISAN OZON STRATOSFER DI INDONESIA - johan Muhamad; Novita Ambarsari (Lembaga Penerbangan dan Antariksa Nasional, 2011)
Ozone data from Ozone Monitoring Instrument (OMI) and Microwave Limb Sounder (MLS) Aura satellite were used to investigate the impacts of the very intense Solar Proton Events (SPE) 15-25 January 2005 on the stratospheric ozone in Indonesia. From the ozone vertical profiles along the SPEs period, the decreasing of ozone concentration was observed after the peak of the SPEs. This ozone decrease was associated with the increase of NO2 and HO2 concentration which was produced due to the ionization by the energetic protons. The ozone decrease was also identified by analyzing the spatial column amount ozone in Indonesia. The ozone decrease after the SPEs was about 8 percent from the average of daily column amount ozone before the SPEs. The very high energetic protons from the SPEs were suspected to be responsible for the possibility of the proton precipitation into the low latitude regions. Keywords: Solar Proton Event, Stratospheric ozone depletion, Low latitude proton precipitation